Secular state and freedom of religion in Brazil: The Brazil-Holy See Concordat and the “General Law of Religions” - Jose Ivo Follmann (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
This article aims to explore some issues about laicity and religious freedom, the concordat signed between the Brazilian State and the Vatican, and the controversies arising from the proposal of the General Law of Religions. At the same time, it affirms the existence of multiple and divergent senses of laicity, allows observation of different agents in the search for marking, setting, updating, correcting and regulating its application by the State. Catholic and Evangelical activism has generated a lot of contradictory effects. There is a resurgence of religious disputes with consequences in the public sphere, especially in the political arena.